2022
DOI: 10.1002/jpen.2393
|View full text |Cite
|
Sign up to set email alerts
|

Energy expenditure in COVID‐19 mechanically ventilated patients: A comparison of three methods of energy estimation

Abstract: Background Indirect calorimetry (IC) is the gold standard for measuring resting energy expenditure. Energy expenditure (EE) estimated by ventilator‐derived carbon dioxide consumption (EEVCO 2 ) has also been proposed. In the absence of IC, predictive weight‐based equations have been recommended to estimate daily energy requirements. This study aims to compare simple predictive weight‐based equations with those estimated by EEVCO 2 and IC in mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Recently, an alternative to indirect calorimetry has been described and validated to calculate energy expenditure based on ventilator-derived carbon dioxide production as measured by the built-in capnometer of the mechanical ventilator [ 34 ]. Despite being criticized by some authors [ 35 ], this method was shown to correlate better with indirect calorimetry values than estimates derived from weight-based equations [ 36 ] and has the unique advantage of being easily available at the bedside.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an alternative to indirect calorimetry has been described and validated to calculate energy expenditure based on ventilator-derived carbon dioxide production as measured by the built-in capnometer of the mechanical ventilator [ 34 ]. Despite being criticized by some authors [ 35 ], this method was shown to correlate better with indirect calorimetry values than estimates derived from weight-based equations [ 36 ] and has the unique advantage of being easily available at the bedside.…”
Section: Discussionmentioning
confidence: 99%
“…15,18 Five studies expressed REE in kilocalories per kilogram of BW for nonobese patients or kilocalories per kilogram of adjusted BW (adj-BW) for patients with obesity. 15,[18][19][20] Figure 1 shows that REE generally increased with time. The weighted mean REE (kilocalories per kilogram of BW) of nonobese patients in week 1, week 2, week 3, and week 4 were approximately 21 (range: 18-25), 26 (range: 23-29), 32 (range: [19][20][21][22][23][24][25][26][27][28][29][30][31], and 29 (range: 19-29), respectively.…”
Section: Energymentioning
confidence: 98%
“…The weighted mean REE (kilocalories per kilogram of BW) of nonobese patients in week 1, week 2, week 3, and week 4 were approximately 21 (range: 18-25), 26 (range: 23-29), 32 (range: [19][20][21][22][23][24][25][26][27][28][29][30][31], and 29 (range: 19-29), respectively. 15,[18][19][20] The weighted mean REE (kilocalories per kilogram of adj-BW) of patients with obesity in week 1, week 2, week 3, and week 4 were approximately 19 (range: 18-20), 27 (range: 26-27), 30 (range: 27-33-25), and 29 kcal/kg, respectively. 15,19 There was no association between the severity of organ failure (measured by the Sequential Organ Failure Assessment score [SOFA]) and inflammatory markers such as C-reactive protein and ferritin.…”
Section: Energymentioning
confidence: 99%
See 2 more Smart Citations